The Role of Digital Marketing in Increasing Sales (Case Study on Small and Medium Enterprises at Kerupuk Singkong Cap Tawon) - Anggelina Liuk; Warter Agustim; R Y Susanto (International Research & Development for Human Beings (IRDH), 2026)
This study aims to investigate the role of digital marketing in increasing sales for the cassava cracker SME